2010
DOI: 10.1590/s1516-35982010000100008
|View full text |Cite
|
Sign up to set email alerts
|

Perdas e valor nutritivo de silagens de milho, sorgo-sudão, sorgo forrageiro e girassol

Abstract: RESUMO -Este trabalho foi realizado com o objetivo de avaliar as perdas e o valor nutritivo de silagens de diferentes forrageiras (milho, sorgo-sudão, sorgo forrageiro e girassol) ensiladas no momento ideal de cada cultura. Utilizou-se um delineamento inteiramente ao acaso, com quatro forrageiras e cinco repetições. As forragens foram ensiladas em silos de PVC com 50 cm de altura e 10 cm de diâmetro, providos de válvula de Bunsen, que foram armazenados por 60 dias. As perdas por gases e por efluente foram aval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
0
29

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 20 publications
7
22
0
29
Order By: Relevance
“…The inclusion of 30% glycerol promoted drop in pH to near-optimal levels. Oliveira et al (2010) and Junior, Siewerdt and Harthmann (2008) obtained values of sunflower silage pH 4.3 and 4.5, respectively.…”
Section: Parametermentioning
confidence: 93%
See 2 more Smart Citations
“…The inclusion of 30% glycerol promoted drop in pH to near-optimal levels. Oliveira et al (2010) and Junior, Siewerdt and Harthmann (2008) obtained values of sunflower silage pH 4.3 and 4.5, respectively.…”
Section: Parametermentioning
confidence: 93%
“…The corn silage DM content was higher when compared to the sunflower silage for all levels of glycerol inclusion. Oliveira et al (2010) in a comparative study on the nutritional quality of different types of silage reported lower DM for sunflower silage (22-25% DM) to be frequent, since the structure of this plant tissue has large amounts of moisture. Factors such as low-DM, temperature rise inside the silo and high buffer capacity of the forage can promote development of Clostridium bacteria which ferment sugars, proteins and produce lactic and butyric acids.…”
Section: Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…Desta forma, cresce a demanda por volumosos como a utilização de silagens (1) . Para melhorar a disponibilidade de forragem ao longo do ano, uma estratégia viável é a ensilagem do excedente de pasto produzido no período chuvoso para ser utilizado no período seco.…”
Section: Introductionunclassified
“…Oliveira et al (13) recomendaram a utilização de plantas com aproximadamente 30% de matéria seca para a ensilagem, pois o estádio de desenvolvimento interfere no teor de MS da silagem e na proporção de grãos na silagem.…”
Section: Resultsunclassified